2015
DOI: 10.1093/cid/civ260
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Zidovudine and Heart Anomalies in the ANRS French Perinatal Cohort and the Nested PRIMEVA Randomized Trial

Abstract: NCT00424814.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…ZDV and didanosine (ddI), drugs that were introduced in the 1990s have only recently shown associations with congenital cardiac defects and cancer, [51,52] respectively, which would not have been apparent without many years of data. Given the changing drugs and changing populations without safety data from clinical trials, ongoing ARV safety surveillance in pregnancy is clearly needed.…”
Section: In-utero Antiretroviral Therapy Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…ZDV and didanosine (ddI), drugs that were introduced in the 1990s have only recently shown associations with congenital cardiac defects and cancer, [51,52] respectively, which would not have been apparent without many years of data. Given the changing drugs and changing populations without safety data from clinical trials, ongoing ARV safety surveillance in pregnancy is clearly needed.…”
Section: In-utero Antiretroviral Therapy Exposurementioning
confidence: 99%
“…The study has provided critical insight on the link between preterm birth and in utero ART exposure, and birth weight, which was not found to be associated with ART in this cohort [64]. Due to its large size, this study has also allowed evaluation of rarer adverse endpoints, such as congenital heart defects and cancer [13,52,65,66]. Although infant follow-up is limited to two years, precluding evaluation of most long-term outcomes, examination of cancer risk was possible through linkage with a national pediatric cancer registry.…”
Section: Art Safety Surveillance Programsmentioning
confidence: 99%
“…There have been several recent and notable studies investigating cardiac function in ART-exposed, HEU infants [4851]. While most studies failed to show any evidence of gross cardiac toxicity by echocardiography between children exposed to ART in utero and those who were not exposed, a number of subclinical findings are quite concerning.…”
Section: Cardiac Function and Cardiovascular Disease Riskmentioning
confidence: 99%
“…For example, several studies demonstrated that in utero ART exposure may be associated with some degree of LV diastolic dysfunction, changes in LV shortening fraction, lower stress-velocity z-scores, and posterior wall thickening. One particularly alarming study showed a higher risk of congenital heart disease, particularly ventricular septal defects, among female subjects exposed to ZDV in utero •[51]. The long-term implications of these findings are yet unclear, but the possibility that cardiac contractility may eventually be compromised in some of these HEU patients should be considered and closely monitored.…”
Section: Cardiac Function and Cardiovascular Disease Riskmentioning
confidence: 99%
“…Some epidemiological studies have found that zidovudine use, especially in the first trimester, is associated with modest elevations in the risk of overall malformations,[4] cardiac malformations,[57] and male genital malformations. [8,9] However, a number of other studies have not replicated the increased risk.…”
Section: Introductionmentioning
confidence: 99%